2014
DOI: 10.1002/2014gl061372
|View full text |Cite
|
Sign up to set email alerts
|

Defining a proxy for the interpretation of seismic anisotropy in non‐Newtonian mantle flows

Abstract: Seismic anisotropy can provide unique insights on convection in the upper mantle. Here we study the link between seismic anisotropy and mantle flow using a non‐Newtonian rheology consistent with deformation by dislocation creep. Using analytical first‐order flow models underneath a ridge and in subduction zones, we find that finite strain ellipsoid (FSE) is a robust proxy of seismic anisotropy, both in terms of orientation and strength, for natural strains smaller than ≈ 1. At larger strains, anisotropy aligns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Measurements of seismic anisotropy provide a means to learn about oceanic plate formation and mantle flow. This is possible because the evolution of lithospheric anisotropy is sensitive to a variety of factors including preexisting mantle fabric (Boneh & Skemer, ; Skemer et al, ), the amount of strain the lithosphere experiences (e.g., Hedjazian & Kaminski, ; Ribe, ; Zhang & Karato, ), the magnitude of shear strain relative to the rate of rotation of the strain axes (Kaminski & Ribe, ), and the presence of melt during deformation (Hansen et al, ; Qi et al, ). At the same time, this variety of sensitivities can make the interpretation of anisotropy difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of seismic anisotropy provide a means to learn about oceanic plate formation and mantle flow. This is possible because the evolution of lithospheric anisotropy is sensitive to a variety of factors including preexisting mantle fabric (Boneh & Skemer, ; Skemer et al, ), the amount of strain the lithosphere experiences (e.g., Hedjazian & Kaminski, ; Ribe, ; Zhang & Karato, ), the magnitude of shear strain relative to the rate of rotation of the strain axes (Kaminski & Ribe, ), and the presence of melt during deformation (Hansen et al, ; Qi et al, ). At the same time, this variety of sensitivities can make the interpretation of anisotropy difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Lin and Kuo (; LK16) compared measured ϕ with the infinite strain axis (ISA), a proxy of the finite strain orientation (Hedjazian & Kaminski, ; Jadamec & Billen, ), in the dynamic model and proposed that ϕ can be explained by strain field in the asthenosphere. In the present study, we take a new approach: the observed ϕ and the ISA azimuth ψ are compared along the SKS path, rather than at the station as though the path is exactly vertical.…”
Section: Model Prediction Of ϕmentioning
confidence: 99%
“…For D-Rex, two nondimensional parameters, M* and λ*, are used to simulate dynamic recrystallization via grain boundary migration and nucleation of strain-free grains, respectively. Both parameters influence textural evolution, but M* is most dominant in determining the overall influence of dynamic recrystallization on texture [e.g., Hedjazian and Kaminski, 2014]. Many prior studies have used M* = 125, the value suggested by Kaminski and Ribe [2001] based on comparisons to the experimental results of Zhang and Karato [1995].…”
Section: Implementation Of Previously Published Modelsmentioning
confidence: 99%